O espaço dos possíveis de Steve Jobs: como foi possível a mitificação em torno da imagem da Apple? - Tartas, Felipe dos Santos (2014)
Advertising Apple, inspired by the work of George Orwell's 1984, aired during the telecast of Super Bowl XVIII served as an allegory of the historical configuration of technological sphere of the United States of America at the time. Affectivity and rationality, whereby antagonism in a relational logic defined Apple. The success of Steve Jobs is linked to technological changes in recent years, a greater enchantment that sphere, which reflects the broader social structure of the U.S., means by which it was possible, from the provision of symbolic tools and materials, transmutation of social, energy accumulated in these disputes who have settled there, by Steve Jobs at Apple company. Operation that put himself and his main company prominently.